The Validity of Blended Learning-Based Laboratory Inquiry Learning Tools - Ezha Vandia Sulawanti; Agus Ramdani; Putu Artayasa (IKIP Mataram, 2021)
The purpose of this study was to determine the validity of the blended learning-based laboratory inquiry learning device. This type of research includes research and development. The development research procedure carried out in the development of blended learning-based laboratory inquiry learning tools refers to the 4D development steps, namely define, design, develop and disseminate. The blended learning-based inquiry learning tool developed consists of a syllabus, lesson plans, LKPD, modules, and evaluation instruments. This study only focuses on content and construct validity which were validated by three experts. Based on the results of the validity analysis using the Aiken index and the reliability analysis using the percentage agreement, it was found that the blended learning-based laboratory inquiry learning tool developed had valid and reliable criteria.